Rhabdomyolysis after out-of-water exercise in an elite adolescent water polo player carrying the IL-6 174C allele single- nucleotide polymorphism - Eliakim, A.; Ben Zaken, S.; Meckel, Y.; Yamin, C.; Dror, N.; Nemet, D. (The Journal of Strength and Conditioning Research, 2015)
We present an adolescent elite water polo player who despite a genetic predisposition to develop exercise-induced severe muscle damage due to carrying the IL-6 174C allele single-nucleotide polymorphism, developed acute rhabdomyolysis only after a vigorous out-of-water training, suggesting that water polo training may be more suitable for genetically predisposed athletes.